Characterising the binding interactions and thermodynamics of odour binding protein 3 - Portman, Katherine Louise (2012)
Odour Binding Proteins (OBPs) are found in the olfactory system of a range of species. Whilst invertebrate OBP function is well understood, the exact function of these proteins in the vertebrate nasal mucus is not fully understood. Multiple subtypes of rat OBPs have been identified and found to share less than 30% sequence identity. Studies have suggested each rat OBP binds to particular sets of odours, which may afford them a particularly important role within the olfactory system, pre-sorting odours. This study focuses on OBP3, closely examining the binding interaction of this protein with a range of odours. This has been done using Isothermal Titration Calorimetry which revealed that the binding of the highest affinity ligands, the heterocyclic compounds, is enthalpically driven. A defined odour series, the gamma-lactones showed that despite increasing ligand size and hydrophobicity, the free energy of binding of these ligands is maintained. Interactions with both 2-isobutylthiazole and the gamma-lactones were examinedusing NMR spectroscopy, which required the NMR assignment of OBP3 to be determined. In addition a homology model of OBP3 was created in order to structurally map the per-residue changes of OBP3 upon binding. It has been found that OBP3 is able to subtly adjust in order to accommodate each of these ligands. Protein engineering of the OBP3 binding pocket has been used to highlight the importance of its size and hydrophobicity. The importance of a tyrosine residue that appears to cover the opening to the binding pocket and is conserved across both the aBPs and the lipocalins family they are part of, has been demonstrated. Mutagenesis has also revealed the importance of a number of key residues for the binding of 2-isobutylthiazole. The ability to rationally improve the affinity of OBP3 for a particular odour has also been demonstrated.